(untitled) (International Journal of Engineering and Computer Science, 2017)
Introduction of computer technology in various fields has simplified the job of human being but has also resulted in large amount of digital data. The challenge is managing the large amount of data, i.e. storing and retrieving it. People are sharing, transmitting and storing millions of images every moment. Although data compression is mostly done to avoid occupancy of more memory, and increase capacity of memory devices, The process of reducing data size without losing the crucial information is known as data compression. There is various data compression technique which can use. These techniques can be classified into two types i.e. Lossy and Lossless compression. In this paper some of the lossy image compression is discussed in detail.